Preparation and Characterisation of Crosslinked Natural Rubber (SMR CV 60) and Epoxidised Natural Rubber (ENR-50) Blends - M. SASITARAN; S. MANROSHAN; C.S. LIM; B. N. KRISHNA VENI; S.K. ONG; R. GUNASUNDERI (ASEAN Journal on Science and Technology for Development, 2017)
In this sudy, the influenceof di(tert-butylperoxyisopropyl)benzene (DTBPIB) on the properties of natural rubber (NR) blend with epoxidized natural rubber (ENR) was determined. Fourier transform infrared spectroscopy with attenuated total refletance analysis and gel content confired crosslinking occurred in the rubber blends in the presence of peroxide DTBPIB percentage. Studies including tensile properties, dynamic mechanical properties, thermogravimetric analysis (TGA) and water absorptivity showed the changes in properties of the crosslinked NR/ENR blends. Tensile properties analysis disclosed the improvements in the modulus at 300% elongation and tensile stength with increasing NR ratios. Dynamic mechanical analysis revealed the blends to be incompatible and immiscible, with ENR showing a more viscous behaviour compared to the polymer blends. Thermal properties improved by blending NR with ENR as the onset temperature of NR/ENR: 50/50 was higher than pure NR by approximately 10oC and ENR by approximately 2oC. Water absorptivity experiment revealed a two-fold reduction in the presence of crosslinking for all blend ratios.